Antioxidant treatment after epileptogenesis onset prevents comorbidities in rats sensitized by a past stressful event. (13th March 2019) - Becker, Christel; Mancic, Angelina; Ghestem, Antoine; Poillerat, Victoria; Claverie, Damien; Bartolomei, Fabrice; Brouillard, Franck; Benoliel, Jean‐Jacques; Bernard, Christophe
Summary: Objective: Unresolved past stressful events can induce a state of vulnerability to epilepsy and comorbidities. Using an experimental model of stress‐induced vulnerability to depression, we tested whether an antioxidant treatment applied after the onset of epileptogenesis was disease modifying and could prevent the occurrence of comorbidities. Methods: We used social defeat (SD) to trigger a state of vulnerability in half of the SD‐exposed population of rats. One month after SD, we used repeated injections of kainic acid to trigger status epilepticus (SE). One subset of animals was treated after SE during 2 weeks with Tempol, a strong antioxidant. Supradural 24/7 recordings were used to assess the development of epilepsy. We assessed spatial and nonspatial memory as well as a depressionlike profile 6 weeks after SE. Results: Serum brain‐derived neurotrophic factor (BDNF) levels decreased after SD in all animals and recovered to pre‐SD levels 1 month later in half of them (SDN group). The other half kept low serum BDNF levels (SDL group). At that stage, SDN and SDL animals do not present a depressionlike profile. The SDL group was more sensitive than the SDN group to epileptogenic conditions. Following SE, the SDL group displayed accelerated epileptogenesis, a depressionlike profile, and severe cognitive deficits as compared to SDN rats. Transient Tempol treatment was disease‐modifying, reducing the number of seizures, and prevented the development of comorbidities in the SDL group. Tempol treatment normalized oxidative stress in the SDL group to SDN levels. Significance: This study illustrates the disease‐modifying effect of antioxidant treatment after the onset of epileptogenesis in a population rendered vulnerable by past stressful events. The transient treatment decreased seizure burden and had long‐term effects, preventing the occurrence of a depressionlike profile and cognitive deficits. We propose that vulnerability to comorbidities can be reversed after the onset of epilepsy.